Inhibition of endotoxin-induced bacterial translocation in mice. - Deitch, E A (1989)
The primary functions of the gut are to absorb nutrients and exclude bacteria and their products. However, under certain circumstances the gut may lose its barrier function and serve as a reservoir for systemic microbial infections. These experiments were performed to determine the mechanisms whereby endotoxin causes bacteria to escape (translocate) from the gut. Bacteria translocated from the gut to the mesenteric lymph nodes of mice challenged with nonlethal doses of Escherichia coli 026:B6 or E. coli 0111:B4 endotoxin. Physical disruption of the gut mucosal barrier appears to be the primary mechanism whereby endotoxin promotes bacterial translocation. Mucosal injury and endotoxin-induced bacterial translocation were reduced by inhibition (allopurinol) or inactivation (tung-sten diet) of xanthine oxidase activity (P less than 0.01), but were not affected by the platelet-activation factor antagonists, SRI 63-441 or BN 52021. Because the inhibition or inactivation of xanthine oxidase activity reduced both the extent of mucosal injury and endotoxin-induced bacterial translocation, the effect of endotoxin on the gut appears to be mediated, at least to some degree, by xanthine oxidase-generated, oxygen-free radicals.